Intracellular biomineralization in bacteria - Wei Lin (Frontiers Research Topics, 2014)
Bacteria can sequester metals and other ions intracellularly in various forms ranging from poorly ordered deposits to well- ordered mineral crystals. Magnetotactic bacteria provide one example of such intracellular deposits. They synthesize intracellular magnetic minerals of magnetite (Fe3O4) and/or greigite (Fe3S4) magnetosomes which are generally less than 150 nm and organized into one or multiple chain structures. The magnetosome chain(s) act like a compass needle to facilitate the navigation of magnetotactic bacteria by using the Earth's magnetic field. Due to their ubiquitous distribution in aquatic and sedimentary environments, magnetotactic bacteria play important roles in global iron cycling. Other intracellular mineral phases have been evidenced in bacteria such as As2S3, CaCO3, CdS, Se(0) or various metal phosphates which may play as well a significant role in the geochemical cycle of these elements. However, in contrast to magnetotactic bacteria, the biological and environmental function of these particles remains a matter of debate. In recent years, such intracellularly biomineralizaing bacteria have become an attractive model system for investigating the molecular mechanisms of organelle-like structure formation in prokaryotic cells. The geological significance of intracellular biomineralization is important; spectacular examples are fossil magnetosomes that may significantly contribute to the bulk magnetization of sediments and act as potential archives of paleoenvironmental changes. In addition, intracellular mineral deposits formed by bacteria have potentially versatile applications in biotechnological and biomedical fields. After more than four decades of research, the knowledge on intracellularly biomineralizing bacteria has greatly improved. The aim of this Research Topic is to highlight recent advances in our understanding of intracellular biomineralization by bacteria. Magnetotactic bacteria are a system of choice for that topic but other intracellularly biomineralizing bacteria may bring a unique perspective on that process. Research papers, reviews, perspectives, and opinion papers on (i) the diversity and ecology of intracellularly biomineralizing bacteria, (ii) the molecular mechanisms of intracellular biomineralization, (iii) the chemo- and magneto-taxis behaviors of magnetotactic bacteria, (iv) the involvement of intracellularly biomineralizing bacteria in local or global biogeochemical cycling, (v) the paleoenvironmental reconstructions and paleomagnetic signals based on fossil magnetosomes, (vi) and the applications of intracellular minerals in biomaterial and biotechnology were welcomed.